2021
DOI: 10.1021/acs.inorgchem.1c00415
|View full text |Cite
|
Sign up to set email alerts
|

Potent PBS/Polysorbate-Soluble Transplatin-Derived Porphyrin-Based Photosensitizers for Photodynamic Therapy

Abstract: In this study, we addressed an important drawback of our previously reported tetraplatinated (metallo)porphyrin-based photosensitizers (PSs) for photodynamic therapy (PDT), namely, the poor solubility in aqueous media. We aimed to create tetraplatinated porphyrin-based PSs that are soluble in aqueous media modified with polysorbate (Tween) and do not need to be pre-dissolved in organic solvents. A structural optimization of the previously reported PSs resulted in the synthesis of an extremely potent novel porp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…MCTSs treated with 1b and subsequent irradiation with light of 630 nm started dissolving on day three visible in the inflation of the MCTSs to 233% of the initial size followed by a steady decrease in size. This shows that 1b is not just decreasing the growth rate of the MCTSs like cisplatin [40] , but Because MCTSs also simulate tumour hypoxia and proliferation gradients to the centre [51,52] , the observed effectivity in HeLa MCTSs indicated a possible efficiency under hypoxic conditions. To test this hypothesis, the photocytotoxicity determination for compounds 1a and b a 1b in monolayer HeLa cells was repeated under hypoxic conditions (Tab.…”
Section: Photocytotoxicitymentioning
confidence: 87%
“…MCTSs treated with 1b and subsequent irradiation with light of 630 nm started dissolving on day three visible in the inflation of the MCTSs to 233% of the initial size followed by a steady decrease in size. This shows that 1b is not just decreasing the growth rate of the MCTSs like cisplatin [40] , but Because MCTSs also simulate tumour hypoxia and proliferation gradients to the centre [51,52] , the observed effectivity in HeLa MCTSs indicated a possible efficiency under hypoxic conditions. To test this hypothesis, the photocytotoxicity determination for compounds 1a and b a 1b in monolayer HeLa cells was repeated under hypoxic conditions (Tab.…”
Section: Photocytotoxicitymentioning
confidence: 87%
“…As a result of cell attachment interruption on the surface, the liquid overlay culture system facilitates an increase in cell–cell interaction and promotes cell aggregation, leading to the spontaneous formation of spheroids above the non-adherent surface [ 32 ]. For example, a recent study by Schnieder et al [ 34 ] produced HeLa MCTS by the liquid overlay method based on agarose-coated 96-well plates to investigate the phototoxicity of tetraplatinated (metallo) porphyrin-based PS. The study reported a phototoxic index (PI) of 6030 in HeLa cells [ 34 ].…”
Section: Methods For 3d Tumor Generationmentioning
confidence: 99%
“…For example, a recent study by Schnieder et al [ 34 ] produced HeLa MCTS by the liquid overlay method based on agarose-coated 96-well plates to investigate the phototoxicity of tetraplatinated (metallo) porphyrin-based PS. The study reported a phototoxic index (PI) of 6030 in HeLa cells [ 34 ]. Similarly, Karges et al [ 35 ] cultured HeLa MCTS using the liquid overlay technique and evaluated the phototoxic effect of Ru(II) polypyridine complexes with (E,E′)-4,4′-bisstyryl-2,2′-bipyridine ligand [ 35 ].…”
Section: Methods For 3d Tumor Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…An important parameter to evaluate the effect of PSs is the phototoxic index (p.i. ), i.e., the ratio of dark to light toxicity [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Reducing the lipophilicity and minimizing aggregation of the planar PS, for example by PEGylation, plays a critical role for improving PDT therapeutic efficiency and improving the p.i.…”
Section: Introductionmentioning
confidence: 99%